AI ABOLITION AS DECOLONIAL RUPTURE IN AI EMPIRE: RADICAL CYBERPRACTICES FROM BELOW - Tacheva, Zhasmina; Appedu, Sarah; Choi, Jeongbae; Wright, Mirakle; Qin, Yigang (AoIR Selected Papers of Internet Research, 2026)
Existing research has long established that AI is not just a collection of technical tools but an expansive system of governance: what scholars refer to as AI empire - deeply embedded in racial capitalism, carceral logics, colonial control, and heteropatriarchy (Crawford, 2021; Tacheva & Ramasubramanian, 2023). However, much of the critical scholarship in AI studies tends to focus on AI’s most visible harms, such as mass surveillance, biased decision-making, and AI’s role in warfare. This paper argues that AI empire’s violence is far more insidious and pervasive, and extends beyond these explicit harms to algorithmic systems that actively shape docile populations and reinforce existing hierarchies of power (Benjamin, 2019). In response, this work positions AI abolition as a necessary and decisive rupture that rejects predominantly reformist interventions, which merely tweak AI’s carceral mechanisms without challenging the underlying structures of domination. Drawing from the decolonial queer feminist scholarship of early cybercultural critics like Chela Sandoval, this paper examines historical counter-technological practices, including Indigenous computing, socialist cybernetics, and feminist teleconferencing, as alternative models for technological futures that reject extractive AI governance. By reclaiming these insurgent histories, this work reframes AI abolition as an ongoing practice of refusal and reimagination and argues that meaningful technological transformation must go beyond surface-level mitigation efforts to fundamentally disrupt the oppressive logics embedded in hegemonic AI cultures.